Differences in Organizational Behavior amongst Startup and Established Company: A Literature Review - Astuti, Tri; Helmi, Avin Fadilla; Riyono, Bagus (Buletin Psikologi, 2023)
Two business models differ significantly between an established company and a startup in the industrial world. There are notable distinctions between the two business models in several areas that, upon closer examination, can offer entrepreneurs, practitioners, researchers, and the government guidance in devising the most appropriate business model approach. The subsequent goal of this research is to conduct a more thorough analysis of the organizational behavior variations between startups and larger businesses. Because numerous research sources have been completed but have yet to be more thoroughly consolidated, this study uses a literature review approach to address the research issues posed. This approach is also capable of identifying variations from the given context. According to the study, established businesses and startups differ in three ways. The study's findings, to be more precise, revealed variations in the two business models' definitions and life cycles. Second, the social relations system and structure derived from these two company models differ. Finally, these two categories of businesses must deal with varying degrees of uncertainty in the workplace. This research suggests that by examining the distinctions between large and small companies which are just starting, business actors can benefit from this research and use it as a guide to improve organizational performance.